Destructive Phytophthora on orchids: current knowledge and future perspectives - Bag, Tusar Kanti; Dutta, Pranab; Hubballi, Manjunath; Kaur, Ravpreet; Mahanta, Madhusmita; Chakraborty, Ardhendu; Das, Gitasree; Kataky, Madhusmita; Waghunde, Rajesh (Frontiers in Microbiology, 2024)
Anton de Bary first coined the genus, Phytophthora, literally means "plant destroyer", viewing its devastating nature on potato. Globally plants face enormous threat from Phytophthora since its occurrence. About a century ago, Phytophthora palmivora (Petch, 1921) first reported on Dendrobium maccarthiae in Sri Lanka. Since then, members of beautiful flowering crops of family Orchidaceae facing the destructive threat of Phytophthora. Several Phytophthora species have been recorded to infect orchids with economic loss worldwide. To date, orchids are attacked by 12 species of Phytophthora. Five Phytophthora species (P. palmivora, P. nicotianae, P. cactorum, P. multivesiculata, P. meadii) are the major pathogenic Oomycetous Chromista" rather than true fungi frequently occurred on Orchidaceae. Phytophthora palmivora (having ~32 orchid host genera in 15 countries), Phytophthora nicotianae (having ~15 orchid host genera in 16 countries), Phytophthora cactorum (having ~43 orchid host genera in 6 countries), Phytophthora multivesiculata (having 2 orchid host genera in 5 countries) and Phytophthora capsici (having 2 orchid host genera in all Vanilla growing countries) are potential destroyers of Orchidaceae. Most of them are water loving Oomycetes causes disease in moist environments (> 80% RH) at 16-28 o C. In artificially constructed orchidaria, anthropogenic factors are mostly contributed in the dissemination Phytophthora diseases in addition to many other factors. Water management, clean cultivation and agro-chemicals are the major options for effective management of orchid Phytophthora, as the eco-friendly management options like development of resistant hybrids/cultivars, biological disease management, transgenic approaches, RNAi technology remained in the infant stage. In this review, we intended to highlight the insight of Phytophthora diseases associated with orchid disease with reference to the historical aspect of the diseases, symptoms and signs, the pathogens, taxonomy, geographic distribution, host range within the Orchidaceae, pathogen identification, molecular diagnostics, mating types and races, management options and strategies and future perspectives.The consolidated information on various aspects of the destructive hids is lacking in the literature. This review aims to highlight recent developments in thora diseases associated with orchid with reference to symptoms and signs, the pathogens, ta onomy, geographic distribution, host range within th and future perspectives.